Gendered identities in the consumption of mobile phones among youth in Botswana. (1st June 2017) - Lesitaokana, William O.
Research on the interactive relationship between youth and mobile phones has demonstrated that mobile devices have become indispensable in many aspects of youth lifestyles. Despite this, there is currently very limited research on mobile phone cultures in Sub-Saharan Africa. This article considers two very distinct gendered identities resulting from mobile phone consumption among students in Botswana: one involving adolescent females using colourful mobile phones and brightly coloured casings for their handsets as symbols of fashion and modernity, and the other relating to their male counterparts mostly preferring to own smartphones that are costly as these handsets gratify their sense of having a contemporary personal status. I then go on to demonstrate that although the findings from this study are analogous to those from similar studies worldwide, to a large extent, the gendered identities exhibited among youth in Botswana contexts are predicated on conventional practices entrenched in the traditional Tswana lifestyle.